Euro 1999 : 25 March 1998 : report on progress towards convergence and the recommendation with a view to the transition to the third stage of economic and monetary union (Office of the Official Publications of the EuropeanCommunities LuxembourgLU, 1998)
Takes stock of the progress made by the Member States in fulfilling their obligations regarding the achievement of economic and monetary union. Recommends to the Council that the following Member States adopt the euro on 1 January 1999 : Belgium, Germany, Spain, France, Ireland, Luxembourg, the Netherlands, Austria, Portugal and Finland.
Contents: Part 1 : Recommendation. - Part. 2 : report